Transport of fluorobenzoate tracers in a vegetated hydrologic control volume: 1. Experimental results. Issue 4 (26th April 2015) - Queloz, Pierre; Bertuzzo, Enrico; Carraro, Luca; Botter, Gianluca; Miglietta, Franco; Rao, P. S. C.; Rinaldo, Andrea
Abstract: This paper reports about the experimental evidence collected on the transport of five fluorobenzoate tracers injected under controlled conditions in a vegetated hydrologic volume, a large lysimeter (fitted with load cells, sampling ports, and an underground chamber) where two willows prompting large evapotranspiration fluxes had been grown. The relevance of the study lies in the direct and indirect measures of the ways in which hydrologic fluxes, in this case, evapotranspiration from the upper surface and discharge from the bottom drainage, sample water and solutes in storage at different times under variable hydrologic forcings. Methods involve the accurate control of hydrologic inputs and outputs and a large number of suitable chemical analyses of water samples in discharge waters. Mass extraction from biomass has also been performed ex post. The results of the 2 year long experiment established that our initial premises on the tracers' behavior, known to be sorption‐free under saturated conditions which we verified in column leaching tests, were unsuitable as large differences in mass recovery appeared. Issues on reactivity thus arose and were addressed in the paper, in this case attributed to microbial degradation and solute plant uptake. Our results suggest previously unknown features of fluorobenzoate compounds as hydrologic tracers, potentially interesting for catchment studies owing to their suitability for distinguishable multiple injections, and an outlook on direct experimental closures of mass balance in hydrologic transport volumes involving fluxes that are likely to sample differently stored water and solutes. Key Points: Experimental storage and sampling of water and solutes Degradation and uptake of fluorobenzoate tracers in unsaturated conditions Measures of solute uptake by vegetation are essential to flow kinematics